2019
DOI: 10.3390/cli7030040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Twenty-First Century Crop Yields in the U.S.

Abstract: Crop yields are strongly dependent on the average climate, extreme temperatures, and carbon dioxide concentrations, all of which are projected to increase in the coming century. In this study, a statistical model was created to predict US yields to 2100 for three crops using low and high-emissions future scenarios (RCP 4.5 and 8.5). The model is based on linear regressions between historical crop yields and daily weather observations since 1970 for every county in the US. Yields were found to be most strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
5
20
0
Order By: Relevance
“…Climate parameters such as increased temperature, high or low precipitation as well as extreme weather events adversely affect crop productions, thus challenging food security [4]. Studies projected that increased atmospheric CO 2 concentration would have a mixture of positive and negative effects on rice production, consumption, distribution as well as national development [17][18][19][20]. Extreme weather events due to climate change alter the food production, consumption, trade, and distribution patterns, thus challenging poverty eradication, food security, and sustainable development [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Climate parameters such as increased temperature, high or low precipitation as well as extreme weather events adversely affect crop productions, thus challenging food security [4]. Studies projected that increased atmospheric CO 2 concentration would have a mixture of positive and negative effects on rice production, consumption, distribution as well as national development [17][18][19][20]. Extreme weather events due to climate change alter the food production, consumption, trade, and distribution patterns, thus challenging poverty eradication, food security, and sustainable development [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of temperature on plant development can be due to higher average temperatures or short-term increases in temperatures above the optimum range [4,5]. Some crop models predict higher yields in the short-term with climate change and lower yields in the long-term, while other models predict lower yields across both periods or even under current conditions [6][7][8][9][10][11][12][13][14]. There can be difficulties in predicting yields under climate change because the changes in CO 2 and temperature, etc.…”
Section: Introductionmentioning
confidence: 99%
“…If this occurs in Cannabis plants, then it would ultimately influence the quantity and type of insects such as pollinators on hemp plants. Furthermore, it has been predicted that the US may experience warmer winters, resulting in diminished vernalization [ 82 , 83 ], a process required to promote flowering in certain types of crops. It is suggested that hemp varieties resistant to drought, high soil salinity, cold, heat, humidity, and common pests and diseases should be selected [ 84 ].…”
Section: Corn Earworm and Hemp: Potential Effects Of Climate Changementioning
confidence: 99%